Measuring experienced levels of pleasure, productivity, restoration, and social connection during occupational performance - Berg, Brett, author; Atler, Karen E., advisor; Fisher, Anne G., advisor; Hooper, Barbara R., committee member; Coatsworth, J. Douglas, committee member (Colorado State University. Libraries, 2020)
Background: The Occupational Experience Profile (OEP) is a new assessment tool designed to evaluate levels of pleasure, productivity, restoration, and social connection that people experience during their occupational performances. The OEP was based on a previously published assessment of occupational experience, the Daily Experiences of Pleasure, Productivity, and Restoration Profile (PPR Profile). Based on my review of the literature, I found that there was a need (a) to revise the PPR Profile rating scales and items, and (b) to add a scale of social connection. Consequently, the PPR Profile was revised and given a new name, the Occupational Experience Profile. No research has been conducted prior to this dissertation to examine the psychometric properties of the OEP. The overall aim of this dissertation, therefore, was to evaluate aspects of validity and reliability of the OEP. Methods: This dissertation was comprised of three studies involving 58 occupational therapy students from a university in the Northeastern United States. Each study contributed in a different way to the validation of the OEP. In the first two studies, Rasch analyses were used to examine aspects of validity and reliability of (a) four discrete experience scales (pleasure, productivity, restoration, and social connection) and (b) a composite OEP scale comprised of the items from all four scales. In the third study, cluster analyses were used in an attempt to identify subgroup patterns of occupational experiences described in terms of relative levels of pleasure, productivity, restoration, and social connection. Results: The results of the first two studies provided preliminary evidence to support the use of the OEP to generate valid and reliable discrete and composite measures of occupational experiences. The discrete OEP scales demonstrated sound psychometric properties in terms of rating scale functioning, unidimensionality, and reliability. The composite OEP rating scale demonstrated effective rating scale functioning and the resulting measures were even more reliable than the discrete OEP measures. The results of the second study also identified a potential risk to unidimensionality of the composite OEP scale. The third study provided inconclusive evidence to support the use of the OEP for identifying subgroup patterns of occupational experiences. More specifically, results of the third study indicated the presence of two subgroups, but the subgroup patterns of occupational experiences were essentially parallel, differing merely by overall level of occupational experience. Conclusion: This dissertation provided preliminary validity and reliability evidence to support the use of the OEP to generate discrete and composite measures of occupational experience, but inconclusive evidence that the OEP could be used to identify subgroup patterns of occupational experiences. The discrete OEP measures have the potential to be used to create profiles of occupational experiences that describe participants' relative levels of pleasure, productivity, restoration, and social connection experienced during their occupational performances. Additionally, the composite OEP scale potentially could be used to generate even more sensitive measures. Considered together, with further research, the discrete and composite OEP measures have the potential to be used in occupational therapy practice and research.
Keywords: occupational experience; occupational therapy; validity; occupational patterns; instrument development; Rasch measurement